Using Moodle - Cole, Jason R. (O'Reilly, 2008)
"Developed by an extremely active open source community, Moodle is a popular Course Management System (CMS) that's ideal for creating dynamic online learning communities and for supplementing face-to-face learning. Moodle gives teachers and trainers a set of web-based tools for an array of activities, such as forums, messaging, quizzes, assignments, wikis, blogs, and databases." "Using Moodle, Second Edition, is a comprehensive, hands-on guide with plenty of examples, screenshots, best practices, and suggestions for using Moodle tools effectively and creatively."--Jacket